Anotação digital e produção textual: o uso da DLNotes2 na construção de resumos - Sippel, Juliano (2019)
In this research we carried out a practical study of reading argumentative text mediated by a digital annotation tool, the DLNotes2, aiming a subsequent production of a text of the genre summary. Our goal was to verify if annotations made on DLNotes2 are recovered by the student in their text production, possibly indicating an aid to their writing production planning. This because we believe such annotations support the construction of the summary, for they are useful to the understanding of structural parts of the original text as it allows subsequent consultation by the student. To the effect of our research we conducted an activity with students of the first period of the course of Letters of UTFPR (campus Curitiba), held via Google Forms and DLNotes2. While using the tool, we asked participants to annotate theory, arguments and counterarguments listed by the author of an opinion article and any other aspects they judged important to their comprehension of it. On a second activity the students produced a summary of the article. We identified if the annotations helped and in fact are present on the students summaries, corroborating to our hypothesis that DLNotes2 can be used as a form of support on writing planning. It permeated our dissertation a reflection on the instrumentalization of the genre summary -for we understand, based on a theoretical revision on technology, and language, that text genre can be considered a technology that mediate our actions in the world; in addition we consider writing itself a technology -, the theoretical basis on New Literacy Studies and the digital literacy, besides a reflection on digital annotation tools.